The Schreber case : towards a philosophical construction of madness - Lees, Lorna (Trinity College (Dublin, Ireland). Philosophy Department, 2009)
Daniel Paul Schreber, lawyer and judge, is better known as a "psychiatric patient par excellence". Schreber's case is also interesting in terms of the debate as to what constitutes health and what, disease. The three main philosophical accounts of disease - naturalist, normativist, and Wakefield's hybrid theory - are examined. None of them, however, are able to satisfactorily explain Schreber's complex case. The key issue is that, following Schreber's second breakdown, he was well enough to leave the Asylum but he maintained his delusional framework and adhered to the strictures it placed upon him. How can a person be neither strictly sane nor mentally ill? An alternative analysis of disease is examined. Ereshevsky's claim is that the objective facts about a bodily or a mental state must be taken into account when discussing disease, but these objective state descriptions ought not to be conflated with the subjective experience of the patient or, where applicable, that of the medical practitioners involved.
Keywords: Philosophy, Ph.D.; Ph.D. Trinity College Dublin.